Queer provocations! Exploring queerly informed disruptive pedagogies within feminist community-higher-education landscapes. Issue 1 (2nd January 2017) - Quilty, Aideen
Abstract : Deborah Britzman, over 15 years ago in her insightful essay "Is There a Queer Pedagogy? Or Stop Thinking Straight", posed questions that continue to resonate (Britzman, Deborah P. 1998. Curriculum: Toward New Identities, edited by William Pinar, 211. New York: Routledge). What if lesbian and gay theories were understood as offering a way to rethink the very grounds of knowledge and pedagogy in education? And, conceptually speaking, what is required to refuse the unremarked and obdurately unremarkable straight educational curriculum? That these remain provocative questions for educators speaks to the reality that 'heteronormativity is still a (spatial!) structure that conceals, denies and erases' (Brown, Gavin, and Kath Browne. 2011. "Sedgwick's Geographies: Touching Space." Progress in Human Geography 35 (1): 125). This article offers a consideration of norm-challenging 'disruptive' pedagogies within a particular context of feminist community-based Irish higher education. I ask how can feminist empowerment education look to, and draw from, the destabilising potential of queer to advance its commitment to 'disruptive' pedagogies (Zemblyas, Michalinos, and Megan Boler, eds. 2002. "On the Spirit of Patriotism: Challenges of a 'Pedagogy of Discomfort'." Teachers College Record On-line, 10, from Special Issue on Education and September 11 (http://tcrecord.org)). To ground this particular exploration I re-consider four elements of Megan Boler's seminal work on pedagogies of discomfort: the imaginary; critical reflection; emotions; and a call to action.